Analisis Kepuasan Mahasiswa Program Studi S1 Teknik Industri di Universitas Xyz Berdasarkan Metode Service Quality - Meidianti, Ulfa; Saputra, Rahmat (Program Studi Teknik Industri Universitas Muhammadiyah Tangerang, 2024)
This research aims to analyze the level of satisfaction of students in the Industrial Engineering Undergraduate Study Program at XYZ University with the services they receive, using the Service Quality (ServQual) framework. Student satisfaction is measured based on five dimensions of service quality, (tangibles, reliability, responsiveness, assurance, empahty). The research method used is a qualitative study with a descriptive approach. Data was collected through questionnaires distributed to students. The results of the analysis show that students consider the aspect of reliability in academic services important, followed by responsibility, assurance, empathy, and physical evidence. This research provides input for university management to improve the quality of academic services, so that it can increase student satisfaction and support the smooth teaching and learning process in the campus environment. Keywords: Analysis of student satisfaction, service quality, expectations